Development of participatory curriculum toward empowered, competent and confident barangay health workers - Pangilinan, Cecil Margarette E.
The purpose of this study is to develop, implement and assess a training course that is participatory and responsive to the needs of the BHWs and the community they serve. Specifically, it aims to identify the training needs of barangay health workers of Barangay Casilagan, Naguilian, La Union in relation to their expected roles and responsibilities, develop through participatory process a curriculum for the barangay health workers according to identified needs, determine the effectiveness of the curriculum for achieving the intended learning outcome and propose a curriculum framework process that ensures participation from curriculum development to implementation and evaluation. The study used Research and Development (R & D) study design and composed of three phases. The first phase is the assessment phase wherein needs were identified based on results of three separate focus group discussions among Barangay Health Workers, Local Government Unit Staff and Household Representatives. The second phase focused on the development of participatory curriculum according to the needs identified and with collaboration of LGU, Trainer, Curriculum experts and researcher. On the last phase, the curriculum was implemented and evaluated. Qualitative analysis was used for data gathered from Phase 1 and Phase 2 while quantitative analysis was used for analysis of Phase 3 data. For the phase 3, the first three levels of Kirkpatrick?s Level of Assessment Model were used. TESDA Certification to assess the skills was used together with the self-assessment scale to determine changes in attitude specifically confidence and empowerment and then analyzed through paired t test. Based on the needs analysis, Hilot Wellness Training program was identified as the most suitable and feasible for BHWs. In Phase 2, the curriculum for Hilot Wellness Training Program was developed and pretested in collaboration with LGU, trainer, curriculum experts, and the researcher. Analysis of pre test data showed effectiveness of the curriculum in achieving intended learning outcomes. Results of Level 1 evaluation suggest that participants were generally satisfied with the training based on the mean score of 54.2 Three areas of learning (Level 2) were evaluated. Level 2 (Knowledge) evaluation result suggested that there was significant improvement of knowledge among the BHWs before and after the training at p value of 0.001. Achievement of skills (Level 2) was assessed and achievement certified by TESDA as evidenced by the certificate awarded to BHWs. Comparison of empowerment pre test and post test results suggested that participants feel more empowered after undergoing the training. Confidence pre test and post test scores suggested that there was a significant improvement in terms of confidence level before and after the implementation of the curriculum. In terms of clients? perception of BHWs, results also showed significant improvement of BHWs behavior as perceived by the clients after the training. Conclusion: A curriculum developed with different stakeholders can ensure relevance to the needs of both trainers and their clients. A training conducted based on a participatory curriculum resulted to significant and positive achievement of intended learning outcome.